Effectiveness of Health Promotion Model-Based Educational Video on Adolescent Knowledge and Attitude Regarding Stunting Prevention: A Case Study in Ponorogo, Indonesia - Denis Khorudin; Sajidan; Ratih Puspita Febrinasari; Revi Gama Hatta Novika; Hari Wahyu Nugroho (Journal of Health Promotion and Behavior, 2026)
Background: Indonesia’s stunting prevalence stands at 19.8%, far above the national target of 14%. Adolescents, as future mothers, represent a critical yet underutilized upstream prevention target. No study has previously integrated all constructs of the Health Promotion Model (HPM) into an educational video for adolescent stunting prevention. This study aimed to develop a valid HPM-based reproductive health education video and evaluate its effectiveness on adolescent knowledge and attitudes. Subjects and Method: A sequential exploratory mixed-method study applied the Analysis, Design, Development, Implementation, and Evaluation in Research and Development (ADDIE R&D) framework combined with a quasi-experimental with control group design, was conducted at two High Schools in Ponorogo, Indonesia. The intervention group consisted of 55 senior high school students, while the control group consisted of 55 vocational high school students. Study was carried out from September 2025 to March 2026. Content validity was assessed by two experts: a health promotion specialist and a visual media specialist. Quantitative data were analyzed using the Wilcoxon signed-rank test (within-group) and Mann-Whitney test (between-group). Results: Expert validation demonstrated excellent content validity, with a perfect Scale-Level Content Validity Index based on the average method (S-CVI/Ave = 1.00), and no revisions were required. Knowledge scores increased significantly in the intervention group (p < 0.001). Attitude scores also improved significantly in the control group (p<0.001). However, the post-test comparison between the intervention and control groups showed a statistically significant difference (p <0.001), with the intervention group achieving superior outcomes. Conclusion: The Health Promotion Model (HPM)-based reproductive health educational video demonstrated excellent content validity and significantly improved adolescents' reproductive health outcomes. Therefore, its integration into school-based health promotion programs is recommended to enhance reproductive health education among adolescents.